ANALISIS CEMARAN BAKTERI Coliform DAN Escherichia coli DARI SAMPEL ES BATU PADA PEDAGANG MINUMAN KAKI LIMA DI SEKITAR PASAR CIRACAS JAKARTA TIMUR MENGGUNAKAN METODE MOST PROBABLE NUMBER (MPN) - Dwitami, Ananda Rizki; Achmadi, Achmadi; Wijayanti, Dian Rachma (BIOPENDIX: Jurnal Biologi, Pendidikan dan Terapan, 2024)
Background: Water is a basic need of living things. Water is a liquid, when it freezes it turns into ice cubes. People often use ice cubes as a drink additive to give a fresh taste. The process of freezing ice cubes cannot destroy bacteria, many bacteria can live for a long time at low temperatures. This study aims to determine the contamination of Coliform and Escherichia coli bacteria in ice cubes sold by street vendors around Ciracas Market, East Jakarta. Methods: The MPN method is used to determine the range of Coliform bacteria in ice cube samples. E.coli contamination was detected using Eosine Methylene Blue Agar media. This study uses primary data by collecting samples and testing them in the microbiology laboratory. The sampling technique by purposive sampling. The samples used were ice cubes from street vendors around Ciracas Market is 8 samples. Results: 8 positive samples of Coliform bacteria and 5 positive samples of E.coli bacteria. In Sample 5 it has the highest value of 2900 MPN/100 mL. Sample 6 has the lowest value, namely 140 MPN/100 mL. Conclusion: The eight samples exceeded the contamination threshold allowed by Permenkes 416/Men.Kes/Per/IX/1990, that is 0/100 mL. In the EMBA media there were 5 positive samples of E.coli bacteria.